Effect of vacuum packaging on the shelf life of millet incorporated functional paneer - RENGASAMY, PUGAZHENTHI THIRUMALAI (Indian Journal of Dairy Science, 2017)
Functional paneer was developed with the incorporation of different levels (0.5, 1 and 1.5 per cent) millets viz. foxtail, pearl and finger millets and found that the millets could be incorporated up to 1 per cent level in the paneer. Based on sensory evaluation during storage study of paneer, the functional paneer incorporated with different types of millets at 1 per cent level were acceptable up to 5 days and the control was acceptable up to 7 days at 5°C during storage in normal packaging, whereas, the functional paneer was acceptable up to 25 days and the control up to 30 days at 5°C in vacuum packaging. The microbial quality was within the prescribed standard limits of BIS during the study period at 5°C. Ragi (1 per cent) added paneer was superior to the control and other millet added paneer because of the higher yield, fibre content and lower cost of production.